Effect of Cyanobacteria Isolates on Rice Seeds Germination in Saline Soil - Baghdad Science Journal (مجلة بغداد للعلوم)
Cyanobacteria are prokaryotic photosynthetic communities which are used in biofertilization of many plants especially rice plant. Cyanobacteria play a vital role to increase the plant's ability for salinity tolerance. Salinity is a worldwide problem which affects the growth and productivity of crops. In this work three cyanobacteria strains (Nostoc calcicola, Anabaena variabilis, and Nostoc linkia) were isolated from saline soil at Kafr El-Sheikh Governorate; North Egypt. The propagated cyanobacteria strains were used to withstand salinity of the soil and increase rice plant growth (Giza 178). The length of roots and shoot seedlings was measured for seven and forty days of cultivation, respectively. The results of this investigation showed that the inoculation with Nostoc calcicola, Anabaena variabilis, and Nostoc linkia increased root length by 27.0, 4.0, 3.0 % and 39, 20, 19 % in EC5 and 10 (ds/m), respectively. Similarly, they increased shoot length by 121, 70, 55 %, 116, 88, 82 % in EC5 and 10 (ds/m), respectively. In EC15and more concentrations, control rice plants could not grow while those to which cyanobacteria were inoculated could withstand only EC15 but not other elevated concentrations. These results encourage using Nostoc calcicola,Anabaena variabilis, and Nostoc linkia as biofertilizer for rice plant in the saline soil for increasing growth and decrease soil electrical conductivity.